2018
DOI: 10.15244/pjoes/77919
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Copper in Soils from Different Fertilizer Doses in Relation to Environmental Risk Assessment

Abstract: Total copper distribution in the soil profile was determined, depending on the type of soil and Cu dose, 5 years after the application of this element. Soil samples were taken from 5 layers to 50 cm depth from microplots filled with 3 types of soil that 5 years earlier had been treated with 5 doses of Cu: 4, 8, 12, and 16 kg ha-1. There was an uneven distribution of Cu in the soil profile. In general the Cu decreased in the subsurface layers (10-30 cm) and increased in deeper layers (30-50 cm) in relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Together with basic pH values, the presence of multi-heavy metal ions in the soil lead to an increase in the retention of a single metal, mainly as competitive as consequence of the ionic exchange, the principal retention mechanism of heavy metals (Esshaimi et al 2013). Besides, metal leaching from the soil is caused, on the one hand, by leaching pH, while on the other hand, by soil properties and climate factors which also affect the mobility or immobility of metals in the soil (Stanislawska-Glubiak et al 2018). Therefore, heavy metals usually exhibit different leaching characteristics due to different retention pattern of soil matrixes.…”
Section: Leaching Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with basic pH values, the presence of multi-heavy metal ions in the soil lead to an increase in the retention of a single metal, mainly as competitive as consequence of the ionic exchange, the principal retention mechanism of heavy metals (Esshaimi et al 2013). Besides, metal leaching from the soil is caused, on the one hand, by leaching pH, while on the other hand, by soil properties and climate factors which also affect the mobility or immobility of metals in the soil (Stanislawska-Glubiak et al 2018). Therefore, heavy metals usually exhibit different leaching characteristics due to different retention pattern of soil matrixes.…”
Section: Leaching Experimentsmentioning
confidence: 99%
“…The result showed that a high contents of the elements were noted in the surface layer of the sediments which may be affected by weaving industry centers in the Obra River valley in Poland between the 16th and the 19th century. Stanislawska-Glubiak et al (2018) investigated the dynamics of changes in the metal concentrations in the soils contaminated with Cd, Pb, and Zn for a 5 year period. The authors concluded that sandy soil contamination with metals poses a potentially higher threat to humans and the environment than silty soil contamination, and the examination of the sandy soils contamination, as well as of the groundwater occurring in these areas, should be carried out at least once for 5 years, and even more often.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, coexistence and accumulation of trace elements in soil are considered to be very important issues in ecotoxicology [1][2][3][4][5]. This is because of the fact that the specific participation of individual elements' compounds in the soil can influence the process of their cumulation in the so-called critical plant parts (usually underground organs or leaves, but also other morphological parts of the plant), and leads to their undesirable elevated levels [6][7][8][9][10]. As it is known, excess exposure to both essential and toxic elements either via the food chain or through direct exposure by dermal contact can be hazardous to human health [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are important concerns regarding their intensive use due to soil contamination, adverse effects on soil fauna, soil microbiomes, phytotoxicity, and metal residues in food [5,6]. The long-term use of Cu-based fungicides has resulted in an excessive accumulation of Cu in the soils of French and Portuguese vineyards [7,8]. In temperate zones, it has been shown that earthworms are more susceptible to Cu than most other groups of soil invertebrates [9].…”
Section: Introductionmentioning
confidence: 99%